2022
DOI: 10.1017/s1092852922000785
|View full text |Cite
|
Sign up to set email alerts
|

Attentional problems occur across multiple psychiatric disorders and are not specific for ADHD

Abstract: Objective Attentional problems are common and have been associated with multiple psychiatric disorders. This study examined problems of sustained attention across a range of psychiatric disorders using a validated computerized trans-diagnostic attentional paradigm (a continuous performance task). We hypothesized that multiple psychiatric disorders, particularly attention deficit hyperactivity disorder (ADHD), would be associated with pronounced attentional problems. Methods Totally, 576 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a similar vein, adults with PTSD may receive a diagnosis of ADHD when they show distinct hyperarousal symptoms, including severe attentional dysfunction. Research has proven that impaired sustained attention is non‐specific for ADHD and common among multiple other psychiatric disorders, including PTSD (Grant & Chamberlain, 2022). Indeed, the body of research included in this current review shows that attentional difficulties are neither rare nor limited to higher‐order attentional networks among individuals with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, adults with PTSD may receive a diagnosis of ADHD when they show distinct hyperarousal symptoms, including severe attentional dysfunction. Research has proven that impaired sustained attention is non‐specific for ADHD and common among multiple other psychiatric disorders, including PTSD (Grant & Chamberlain, 2022). Indeed, the body of research included in this current review shows that attentional difficulties are neither rare nor limited to higher‐order attentional networks among individuals with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, it would be relevant to derive a but also in individuals with other psychiatric conditions. Previous studies showed consistent findings that attention deficits were not specific for ADHD but occur across multiple psychiatric disorders, including major depressive disorder, anxiety disorders, obsessive-compulsive disorder, and schizophrenia (Carter et al, 2010;Grant & Chamberlain, 2022;Tetik et al, 2022;Wang, Zhou, & Zhu, 2020). These findings indicate that attention deficits may be in the center of neuropsychological syndromes and a core clinical feature in a wide range of psychiatric disorders other than ADHD, which further complicates differential diagnosis.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 56%